The Effect of Different Bait on Squid Fishing Using Totabito - Abdul Muin Lamela; Alfi Sahri Baruadi; Sitti Nursinar (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2020)
The purpose of this study was to determine the effect of different types of bait on the catch of squid (Loligo Sp) using a totabito fishing gear, by comparing and seeing the effect of the catch on each bait used as treatment. This research was conducted in August 2017 - May 2018 in the waters of Tomini Gulf, in Kayubulan Village, Batudaa Beach District, Gorontalo District. The research is an experimental fishing method and uses analysis of variance in the RAL mathematical model. This study used 3 types of bait as treatment, namely mackerel as treatment A, squid as treatment B, shrimp as treatment C. The results showed that, based on the results of analysis of variance (ANOVA), the treatment of different types of bait had a significant effect, significantly different from the catch of squid. Furthermore, based on the results of further tests using the smallest significant difference (LSD), it was found that treatment C was significantly different from treatment A and B. So that treatment C could be used as an effective bait in catching squid. Keywords: Bait; squid; Loligo sp.; totabito.